Problem-Based Learning dalam Pembelajaran Pendidikan Agama Islam: Sintesis Konseptual untuk Pengembangan Pembelajaran Abad ke-21 - Isnaeni Isnaeni; Muhammad Nur Yahya; Besse Marjani Alwi; Ridwan Idris (LP2M Universitas Islam Ahmad Dahlan, 2026)
Islamic Religious Education (IRE) in the 21st century requires instructional approaches that integrate knowledge acquisition, value internalization, and contextual problem-solving. This study aims to analyze the theoretical foundations, relevance, and implementation challenges of Problem-Based Learning (PBL) in IRE through a library research approach using a conceptual literature review. Data were collected from scholarly books and journal articles indexed in Google Scholar, Scopus, ERIC, and Crossref and analyzed using content analysis. The synthesis indicates that PBL is grounded in constructivism, experiential learning, and self-directed learning, which are conceptually aligned with the epistemological principles of Islamic education, particularly tafakkur (critical reflection), tadabbur (contemplation), and ta'aqqul (reasoning). The reviewed literature also suggests that PBL provides a meaningful framework for connecting normative Islamic teachings with contemporary social issues through problem-oriented learning that promotes critical thinking, reflection, collaboration, and value internalization. Furthermore, its implementation is influenced by teachers' pedagogical readiness, curriculum support, authentic assessment practices, and students' learning readiness. These findings offer a conceptual framework to support the development of more contextual, reflective, and student-centered Islamic Religious Education.